The Effect of Work Environment and Work Motivation on Employee Performance at PT Industry Publishing Pokta - Opang Abdul Gopar; Prista Tarigan; Noor Sembiring (Journal of Accounting and Finance Management, 2022)
Work environment and work motivation are one of the factors that influence employee performance, the purpose of this study is to determine the effect of work environment and work motivation on employee performance at PT Pokta Terbit Industri collected data through a questionnaire using a Likert scale, the questionnaire was given to 75 respondents, namely employees of PT Industry Publication Pokta, the number of respondents is based on the slovin formula with an alpha of 10%. Data analysis technique with instrument test, classical assumption test, multiple linear regression test and F test and T test. The results of this study indicate that the work environment and work motivation have a positive and significant effect either simultaneously or partially on employee performance at PT Industry Publishing Pokta.